Постреволюционная действительность глазами „маленького человека”. Мемуарная проза Вениамина Корсака - Bortnowski, Antoni (Studia Rossica Posnaniensia, 2019)
Veniamin Korsak is a writer who represents the Russian literature of the first wave of emigration and is known primarily through a series of five autobiographical no- vels presenting the story of a simple man who went into German captivity during World War I and then returned to Russia, which was overwhelmed by civil war. Korsak’s works are a testimony of a “little man”, looking at reality through the prism of ordinary everyday affairs, instinctively trying to survive in the historical turmoil. This article is an attempt to show the specificity of this perspective on the basis of his novels.